2005
DOI: 10.5694/j.1326-5377.2005.tb07124.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and economic analysis of drug‐eluting coronary stents available in Australia

Abstract: Objectives: To compare the safety, effectiveness and cost‐effectiveness of drug‐eluting coronary stents used in Australia with bare‐metal stents and determine whether the benefits are greater for high‐risk subgroups. Data sources: MEDLINE, Pre‐Medline, EMBASE, Current Contents, CINAHL and the Cochrane Library database were searched to identify eligible randomised controlled trials and systematic reviews published in English between January 1966 and June 2004. Study selection: Seven randomised controlled trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…Marginal improvement in outcomes from DES use in these low‐risk patients is unlikely to be cost‐effective, thus providing the economic basis for current Victorian guidelines. A recent Australian study showed that limiting DES use to patients at the highest risk of restenosis might improve the cost‐effectiveness of DESs in an Australian model based on randomised trial results 29 …”
Section: Discussionmentioning
confidence: 99%
“…Marginal improvement in outcomes from DES use in these low‐risk patients is unlikely to be cost‐effective, thus providing the economic basis for current Victorian guidelines. A recent Australian study showed that limiting DES use to patients at the highest risk of restenosis might improve the cost‐effectiveness of DESs in an Australian model based on randomised trial results 29 …”
Section: Discussionmentioning
confidence: 99%
“…Several economic analyses have been conducted to examine the implications of the use of DES compared with the use of BMS in each country's healthcare system, including Canada, the United Kingdom, the United States of America, Italy, Switzerland, the Netherlands, Australia, and Belgium [3,9-11]. Few studies have concluded that the use of DES is cost-effective when compared with BMS, and most studies concluded that the use of DES is not cost-effective for all patients or lower risk groups, but is (or might be) cost-effective in some high-risk population such as patients with diabetes, small vessels, or long lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This is the basis for altering these same event risks following introduction of DES. The evidence from several meta-analyses of randomized controlled trials that compare DES to ordinary stents is that the use of DES will reduce the risk of restenosis and CABG by about 40% [4][5][6] while another meta-analysis has shown DESs to reduce the risk of repeat PCI by about 79 percent and CABG by 69 percent [7]. In our simulation we have used a risk reduction for repeat CARP (when the first CARP is PCI) of 50%.…”
Section: Modelsmentioning
confidence: 99%
“…Meta-analyses of randomized controlled trials [2] and population based observational studies [3] have already shown that ordinary stents have contributed to a decline in the risk of a repeat CARP. More recent meta-analyses of randomized controlled trials comparing drug-eluting to ordinary stents [4][5][6][7] suggest even greater effectiveness. Moreover, a population based modeling approach has suggested that DES will lead to a further reduction in the need for revision procedures [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation